EFFECT OF TRIMETHOPRIM-SULFAMETHOXAZOLE PROPHYLAXIS ON FEACAL CARRIAGE RATES OF RESISTANT ISOLATES OF ESCHERICHIA COLI IN HIV-INFECTED ADULT PATIENTS IN LAGOS. - Egwuatu, C. C.; Ogunsola, F. T.; Iwuafor, A. A.; Akujobi, C. N.; Egwuatu, T. O.; Nnachi, A. U.; Oduyebo, O. O. (African Journal of Infectious Diseases (AJID), 2016)
Background: The daily use of Trimethoprim-Sulfamethoxazole (TMP-SMX) prophylaxis reduces morbidity and mortality among patients infected with human immunodeficiency virus (HIV) but its impact on increasing antimicrobial resistance rates has been of public health concern, globally. This study investigated the effect of daily TMP-SMX prophylaxis on feacal carriage rates of resistant isolates of Escherichia coli in HIV-infected adult patients in Lagos. Methods: A total of 550 HIV-infected patients with CD4-cell counts of less than 350 cells/mm3 who were eligible for TMP-SMX prophylaxis and attending Lagos University Teaching Hospital, Lagos, Nigeria, were recruited for this study. Stool/rectal swab samples were aseptically collected from the patients and processed using standard methods for culture and sensitivity. Results: There was a baseline Trimethoprim-Sulfamethoxazole resistance rate of 54% which increased to 77.9% in first 3 months, rising to 96.1% by 6 months and all isolates were resistant by the 9th month. There was also evidence of cross-resistance to other antibiotics with significance in association with TMP-SMX resistance (p<0.0001). The Escherichia coli isolates showed a progressive increase in resistance to the tested antibiotics over the 12-month period. The resistance was in the following order: Ampicillin (74% to 82.6% in the first 3 months; 98.3% by the 6th month and 99.4% by the 9th month; all isolates were resistant by the 12th month), Augmentin (32.5% to 47.7% in first 3 months; 76.1% by the 6th month; 86.3% by the 9th month; all isolates were resistant by 12 months), Ceftriaxone (2.0% to 10.8% in first 3 months; 20.6% by the 6th month; 24.2% by the 9th month; 54.3% by the 12 months). Conclusions: The carriage rate of feacal E. coli resistant to TMP-SMX is common before TMP-SMX prophylaxis. Initiation of TMP-SMX leads to further increase in resistance to TMP-SMX and cross-resistance to other antimicrobials.